KONSEP KURIKULUM MUATAN LOKAL KEAGAMAAN SOLUSI PENINGKATAN PEMAHAMAN AGAMA ISLAM - Indana, Nurul; Indah Nur Sholichah, Yekti (ILJ: Islamic Learning Journal, 2023)
This local Islamic religious content is an evolution of the learning system that is generally implemented in all Tsanawiyah madrasas, because from the start it was implemented in a special way. To maintain the madrasah tradition in maintaining the mastery paradigm of "Understanding of Islamic Religion". The research method uses literature research. With analytical content. The new view assumes that the curriculum is not only limited to a number of subjects. However, the curriculum is considered as a learner's learning experience. The curriculum is all activities carried out by students both inside and outside the school as long as these activities are under the responsibility of the teacher and the school. The new view in terms of learning psychology assumes that learning is not just gathering a number of knowledge. However, it is more to the process of changing behavior. The concept of Islamic religious understanding in junior high school is an educational concept that reforms the previously existing pesantren education concept by prioritizing the concept of making the Al-Qur'an the main source of study in learning and making the Al-Qur'an the main source of study. epistemology development of local content development.